Enhancing Junior High School Students’ Speaking Ability through Picture-Series Technique - Hildaini, Nur Amalia; Husairi, Husairi (Lembaga Bale Literasi, 2025)
This study aimed to improve junior high school students’ speaking ability through the Picture Series Technique in EFL classroom learning. The research employed Classroom Action Research (CAR) conducted in two cycles involving 25 eighth-grade students. Data were collected through speaking tests, classroom observations, and field notes. The findings showed that the implementation of picture series significantly improved students’ speaking performance, particularly in fluency, vocabulary, grammar, pronunciation, fluency, comprehension and confidence. Students also demonstrated greater participation and motivation during classroom activities. The study concludes that the Picture Series Technique is an effective strategy for enhancing students’ speaking skills and creating a more interactive learning environment in junior high school EFL classrooms.